2015
DOI: 10.1097/aln.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Perioperative Point-of-Care Ultrasound Training on Anesthesiology Residents

Abstract: Results suggest that a whole-body POC ultrasound curriculum can be effectively taught to anesthesiology residents and that this training may provide clinical benefit. These results should be evaluated within the context of the perioperative surgical home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 49 publications
3
107
0
1
Order By: Relevance
“…This curriculum focuses on the use of POCUS for cardiac, pulmonary, hemodynamic, abdominal, airway, vascular access, and intracranial pressure measurement. 44 Implementation of this simulator-based curriculum for anesthesiology residents resulted in high participant satisfaction, increased knowledge, improvement in image acquisition, and some elements of clinical transferability. 44 In another study performed at our institution, a Fundamentals of Ultrasound Course was created for anesthesia residents during their intern year.…”
Section: Implementing a Pocus Curriculummentioning
confidence: 97%
“…This curriculum focuses on the use of POCUS for cardiac, pulmonary, hemodynamic, abdominal, airway, vascular access, and intracranial pressure measurement. 44 Implementation of this simulator-based curriculum for anesthesiology residents resulted in high participant satisfaction, increased knowledge, improvement in image acquisition, and some elements of clinical transferability. 44 In another study performed at our institution, a Fundamentals of Ultrasound Course was created for anesthesia residents during their intern year.…”
Section: Implementing a Pocus Curriculummentioning
confidence: 97%
“…8 We agree that adequate training is required to be able to confidently identify subtle pathology; however, as stated in our article, it has been shown that novices with limited training (50 examinations) can reliably diagnose important and life-threatening cardiac conditions such as pericardial effusions, left ventricular dilatation, hypertrophy and failure, and right ventricular dilatation. 9 As more medical professions continue to gain early exposure to PoCUS in their medical schools 10 and residency training, 11 there will be an increased awareness of the many strengths as well as limitations associated with FoCUS at the bedside. Ultimately, FoCUS should be seen as one of multiple bedside tools to assess the hemodynamically unstable patient, and all imaging should always be put in clinical context.…”
Section: Reply To Drs Saranteas and Panoumentioning
confidence: 99%
“…13 What should define the scope of practice of anesthesiologists employing basic transthoracic echocardiography protocols such as those contained within popular protocols such as FoCUS or FORESIGHT? 7,14 Although competency is implied for placement and interpretation of waveforms from a pulmonary arterial catheter, previous studies have well demonstrated that many clinicians' aptitudes are in reality far from perfect. 15 Should we assume that competence will be inferred from completion of training via incorporation of perioperative US into core residency training and ABA certification, or will it be necessary to establish a specific competency examination (or modules) to determine minimal standards for providers?…”
mentioning
confidence: 98%
“…[7][8][9] However, the shortcomings of broad-scale adoption of perioperative US are substantial and must be considered. How specific should a perioperative US curriculum be to enhance care and improve outcomes in the hands of general anesthesiologists?…”
mentioning
confidence: 99%